Incidencia del bullying en el aprendizaje de estudiantes de Educación Básica de la Escuela unidocente Corazón del cantón Valencia.” - Rengifo de la Torre, Tatiana Gissela (2021)
This research is aimed at solving the following research problem: How to reduce bullying and its incidence in the learning of students of the single-center school of Basic Education Corazón del Cantón Valencia, Los Ríos province?, Which results in the approach of the objective general: To elaborate alternative solutions to bullying to improve the learning of the students of the single-center school of Basic Education Corazón of the canton of Valencia, Los Ríos province. It is supported by the mixed research approach and from this reference the inductive deductive methods, the survey, the non-participant observation, the analysis of the products of the activity, the survey techniques, the observation file, the specialist criteria, the workshop are used. of socialization with users and descriptive statistics which allowed to develop the research and reach the following conclusions: The design and partial application of the coexistence workshops in the students of the single-teacher school of Basic Education Corazón, as an alternative solution to bullying and Improvement of the students' learning levels turned out to be feasible and feasible and the evaluation of the preliminary results of the coexistence workshops allowed to demonstrate their effectiveness as significant results are achieved in a relatively short time, which will undoubtedly benefit the results of school student learning unitedcen you of Heart Basic Education in the present future.